ANALYSIS OF THE IMPACT OF HUMAN RESOURCES MANAGEMENT ON THE PERFORMANCE OF ORGANIZATIONS-SAMARRA UNIVERSITY AS A MODEL - Nihad K. Hassan (Scholars Digest Publishing, 2024)
This research aimed to analyze the impact of human resource management on the performance of the University of Samarra. Human resource management is one of the crucial aspects in achieving the goals of organizations, achieving excellence and excellence in the higher education environment. This study is based on the University of Samarra as a model for analyzing the relationship between human resource management and the performance of the organization. The study involves the use of multiple data sources, such as employee questionnaires and interviews, to learn about the human resource management practices followed at the university. Data is analyzed using multiple statistical techniques to achieve the main objectives of the research. This research contributes to identifying factors that directly affect the performance of the University of Samarra and understanding how to improve the performance of the organization through the implementation of effective human resource management practices. Some potential issues, such as the quality of recruitment, training, performance appraisal, motivation, and work environment, may be identified as significant influences on university performance. The findings of the study are to provide applicable guidance to improve the performance of the University of Samarra by improving human resource management practices. Improving employee performance and increasing satisfaction can enhance the quality of education and research and raise the university's profile. This research provides a comprehensive analysis of the impact of human resource management on the performance of the University of Samarra. By understanding this relationship, the researcher has implemented robust strategies to improve the university's performance and successfully achieve its goals in a higher education environment.
Keywords: Human Resources Management, Organization Performance, Samarra University